(untitled) (Modern Problems of Metallurgy, 2024)
The challenges facing the Ukrainian education system, particularly in light of demographic changes and the impact of war, are examined in this research. It highlights the potential for optimizing the operation modes of school buildings under conditions of partial occupancy to reduce energy consumption and ensure comfortable conditions for students. Energy modeling analysis using DesignBuilder software shows that the configuration of classrooms significantly impacts the energy efficiency of buildings. The best results for energy efficiency were achieved with rooms stacked on top of each other, outperforming the variant with three rooms on the middle floor by 22.3%, and mixed configurations by 8.5% and 16%. This efficiency is due to minimized contact with unheated premises and maximized solar heat gains. However, without appropriate building upgrades, the use of limited spaces may not provide adequate comfort conditions in colder periods. For the rooms studied (45-48m2), the required heating device capacity to maintain comfortable conditions varies from 7.5 to 10.5 kW, depending on the level of insulation, which is 3-5 times more than the standard capacity for such spaces. Providing comfortable conditions without upgrading the heating system in cold periods is unfeasible, even with high levels of building insulation and a constant heating schedule. Therefore, implementing partial use of school buildings, despite their high potential for energy savings, cannot satisfy student comfort needs without corresponding improvements. Future research could provide a foundation for developing comprehensive strategies for managing school spaces, considering variable building usage conditions and ensuring an optimal combination of energy efficiency, cost-effectiveness, and comfort for students and staff. The findings can be useful for school administrations, local educational authorities, and policymakers in education and energy efficiency. Further studies are suggested to explore the impact of internal wall insulation, increased heating device capacity, and heating unconditioned rooms to a certain temperature level on energy efficiency and comfort conditions in occupied spaces.